Hypoxia induces myeloid‐derived suppressor cell recruitment to hepatocellular carcinoma through chemokine (C‐C motif) ligand 26. Issue 3 (30th June 2016) - Chiu, David Kung‐Chun; Xu, Iris Ming‐Jing; Lai, Robin Kit‐Ho; Tse, Aki Pui‐Wah; Wei, Larry Lai; Koh, Hui‐Yu; Li, Lynna Lan; Lee, Derek; Lo, Regina Cheuk‐Lam; Wong, Chun‐Ming; Ng, Irene Oi‐Lin; Wong, Carmen Chak‐Lui
Abstract : A population of stromal cells, myeloid‐derived suppressor cells (MDSCs), is present in tumors. Though studies have gradually revealed the protumorigenic functions of MDSCs, the molecular mechanisms guiding MDSC recruitment remain largely elusive. Hypoxia, O2 deprivation, is an important factor in the tumor microenvironment of solid cancers, whose growth often exceeds the growth of functional blood vessels. Here, using hepatocellular carcinoma as the cancer model, we show that hypoxia is an important driver of MDSC recruitment. We observed that MDSCs preferentially infiltrate into hypoxic regions in human hepatocellular carcinoma tissues and that hypoxia‐induced MDSC infiltration is dependent on hypoxia‐inducible factors. We further found that hypoxia‐inducible factors activate the transcription of chemokine (C‐C motif) ligand 26 in cancer cells to recruit chemokine (C‐X3‐C motif) receptor 1‐expressing MDSCs to the primary tumor. Knockdown of chemokine (C‐C motif) ligand 26 in cancer cells profoundly reduces MDSC recruitment, angiogenesis, and tumor growth. Therapeutically, blockade of chemokine (C‐C motif) ligand 26 production in cancer cells by the hypoxia‐inducible factor inhibitor digoxin or blockade of chemokine (C‐X3‐C motif) receptor 1 in MDSCs by chemokine (C‐X3‐C motif) receptor 1 neutralizing antibody could substantially suppress MDSC recruitment and tumor growth. Conclusion : This study unprecedentedly reveals a novel molecular mechanism by which cancer cells direct MDSC homing to primary tumor and suggests that targeting MDSC recruitment represents an attractive therapeutic approach against solid cancers. (Hepatology 2016;64:797‐813)